2012
DOI: 10.1002/iroh.201111364
|View full text |Cite
|
Sign up to set email alerts
|

Life History and Secondary Production of Mayflies (Ephemeroptera) Indicate Disturbance in Two Small Carpathian Streams

Abstract: The life histories and the secondary production of 9 mayflies (Ephemeroptera) species were studied at two sites in a submountain stream (West Carpathians, Slovakia). The disturbed site has a deforested and converted to meadows and pastures catchment and the undisturbed one is a well‐preserved submountain stream with 60% of the catchment covered by spruce forests. Differences in the forest cover and in the thermal regime of both streams were reflected in the structural as well as the functional measures. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Approximately 2x higher values of total stonefly abundance, biomass and secondary production were found in undisturbed stream. Bottová et al (2012) found similar differences in mayfly communities between these streams but values of analyzed mayfly parameters were several times higher. Eisendle and Waringer (1999) found similarly higher values of total mayfly abundance compared to stonefly abundance in small alpine sandstone stream.…”
Section: Discussionmentioning
confidence: 59%
“…Approximately 2x higher values of total stonefly abundance, biomass and secondary production were found in undisturbed stream. Bottová et al (2012) found similar differences in mayfly communities between these streams but values of analyzed mayfly parameters were several times higher. Eisendle and Waringer (1999) found similarly higher values of total mayfly abundance compared to stonefly abundance in small alpine sandstone stream.…”
Section: Discussionmentioning
confidence: 59%
“…Representatives of most species of mayflies showed no clear preference as to the nature of the development of the basin on the given sections of watercourses. Many species of the genus Baetis shows a high tolerance to changes in environmental factors within the channel and basin (Bottova et al, 2012). Thus, in the facilities of the lower reaches of streams, where the adjacent part of the basin was agriculturally developed, numerous representaives of the Baetis, as well as Serratella ignita, were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Our measured values of density, biomass and secondary production would be the first published data on E. ujhelyii. The only data on the secondary 322 K. Bottová & T. Derka production of the genus Electrogena from temperate streams were published for the related species Electrogena samalorum (Landa, 1982) (Bottová et al 2012). Other published data are from Dudgeon (1996), who reported 20.6 mg AFDW m −2 for Electrogena sp.…”
Section: Discussionmentioning
confidence: 99%